Where Science Meets Politics: Controversy Surrounding the Relationship Between Population Growth and Climate Change - Carver, Louise (Consilience, 2010)
There is an increasingly vociferous debate about whether population growth is relevant for climate mitigation policy. The production of scientific knowledge about this relationship, its use in policy and public arenas and interpretation by numerous third parties thereafter presents a political and ethical conundrum in which normative values are easily hidden. Rather than assess the evidence for the contribution population growth might make to future greenhouse gas emissions (GHG), and the implicit or explicit population policy implications therein, this paper engages with a sociological analysis of the process of knowledge production to reveal why the controversy persists. This paper seeks to equip policy makers with a framework through which to navigate such values and thus overcome the apparent policy bind on the issue.